Effects of descending positive end-expiratory pressure on lung mechanics and aeration in healthy anaesthetized piglets - Carvalho, Alysson Roncally S. (2006)
ARSC, FCJ, FAB, JHNS and JS performed the experiments. ARSC participated in the design of the study, performed the statistical analysis and wrote the manuscript. FCJ participated in the design of the study, discussed the results and revised the manuscript. AVP designed the experimental setup. FAB and JS participated in the design of the study and discussed the results. RR established the CT protocol and analysis. JHNS discussed the results. AG-N conceived and coordinated the study and helped to write the manuscript. All authors read and approved the final manuscript.